2014
DOI: 10.4049/jimmunol.1302412
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Primes the Pulmonary Environment to IL-1α/CXCR-2–Dependent Nontypeable Haemophilus influenzae–Exacerbated Neutrophilia in Mice

Abstract: Cigarette smoke has a broad impact on the mucosal environment with the ability to alter host defense mechanisms. Within the context of a bacterial infection, this altered host response is often accompanied by exacerbated cellular inflammation, characterized by increased neutrophilia. The current study investigated the mechanisms of neutrophil recruitment in a murine model of cigarette smoke exposure and, subsequently, a model of both cigarette smoke exposure and bacterial infection. We investigated the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 50 publications
2
41
2
1
Order By: Relevance
“…A similar effect of cigarette smoke was observed in humans, where nasal IL-6 expression was decreased in young healthy smokers following nasal inoculation with live attenuated influenza virus (56). In contrast, we have previously shown that alveolar macrophage responses to nontypeable Haemophilus influenzae (NTHi) in the lungs are skewed by cigarette smoke, suppressing the expression of some inflammatory mediators while augmenting that of others, including IL-1␣, which contributed to excessive lung neutrophilia in response to bacterial infection (57). This could be attributed to differential regulation of inflammatory processes by cigarette smoke in the upper and lower respiratory tracts, as suggested by Huvenne et al (58).…”
Section: Figmentioning
confidence: 85%
“…A similar effect of cigarette smoke was observed in humans, where nasal IL-6 expression was decreased in young healthy smokers following nasal inoculation with live attenuated influenza virus (56). In contrast, we have previously shown that alveolar macrophage responses to nontypeable Haemophilus influenzae (NTHi) in the lungs are skewed by cigarette smoke, suppressing the expression of some inflammatory mediators while augmenting that of others, including IL-1␣, which contributed to excessive lung neutrophilia in response to bacterial infection (57). This could be attributed to differential regulation of inflammatory processes by cigarette smoke in the upper and lower respiratory tracts, as suggested by Huvenne et al (58).…”
Section: Figmentioning
confidence: 85%
“…In a recent study, Nikota et al. showed that cigarette smoke primed the lung environment, including IL-1α production by alveolar macrophages and subsequent increased neutrophil mobilization via the chemokine receptor CXCR2 (37). Upon repeated infections with NTHi, smoke-induced inflammation eventually led to increased lung compliance and structural damage.…”
Section: Discussionmentioning
confidence: 97%
“…In a 4 weeks study, concomitant exposure to CS and S. aureus enterotoxin B induced both goblet cell hyperplasia in the airway wall and the formation of dense, organized aggregates of B-and T-lymphocytes (Huvenne et al, 2011). In 8-week exposure models, the combined exposure to CS and NTHi resulted in airway remodeling, increased inflammation, emphysema (Ganesan et al, 2014) and IL-1 driven neutrophilic inflammation (Nikota et al, 2014). Chronic exposure to NTHi lysate caused infiltration with lymphocytes and collagen deposition, but no mucus cell hyperplasia (Moghaddam et al, 2008).…”
Section: Discussionmentioning
confidence: 98%